A new Mexican species of Chrysina Kirby (Coleoptera: Scarabaeidae: Rutelinae), with nomenclatural changes, new records, and a key to the C. quiche species group - Mora-Aguilar, Eder F.; Curoe, Daniel; Delgado, Leonardo; Ramírez-Ponce, Andrés (Zootaxa, 2018)
Chrysina chimalapensis new species (Coleoptera: Scarabaeidae: Rutelinae: Rutelini), from the region of Chimalapas, Oaxaca, Mexico is described and illustrated. A key to the species of the C. quiche species group is included. Plusiotis neotenochca Morón & Nogueira is placed as a new junior synonym of Chrysina paulseni Hawks, and C. aenigmatica (Morón) as a new junior synonym of C. modesta Sturm. Chrysina benesi from Guatemala, and C. quetzalcoatli from Nicaragua are recorded as new country records. Chrysina quetzalcoatli Morón and C. triumphalis Morón are also recorded for the first time for the state of Oaxaca, Mexico, and C. victorina (Hope) for the state of Veracruz, Mexico.